Title: Root canal treatment for a lengthy maxillary canine of 37 mm. Case Report. - Hussain, Shahad E.; Awooda, Elhadi M. (Hasanuddin University, 2020)
Objective: Very long teeth present challenging in endodontic treatment. It necessitates modification of the instruments and techniques to negotiate the canal and to obturate to the full working length. This case aims to perform root canal treatment (RCT) of a lengthy maxillary canine of 37 mm length.Methods: A 75-year old man came for a filling of decayed upper front teeth. Radiographically, the right canine showed an abnormality in length. Clinically, it was carious, not tender to percussion, and diagnosed as asymptomatic irreversible pulpitis with normal apical tissues. Results: This case illustrated the use of hand H-files (ISO) with the removal of the plastic cable and preparation of the canal by push – pull movement and obturation conventionally through vertical and lateral condensation techniques. CBCT was used to assess treatment outcome. Conclusion: RCT of a very long tooth can be performed by instrument cable removal technique (ICRT) to achieve good quality and better outcomes.